Kondisi Sosial-Ekonomi Dan Potensi Pembangunan Kabupaten Bima - Jasman Jasman; Arman Arman (Universitas 17 Agustus 1945, 2023)
This study aims to examine the socio-economic conditions and potential development of Bima Regency, as well as realizing real policies to increase development in the district. A mixed research design was used, which combined qualitative and quantitative data collection methods. Data was collected through surveys, interviews, and secondary sources, and analyzed using descriptive statistics and content analysis. The findings reveal that Bima District has several development potentials, including its strategic location, natural resources, and human capital. However, this district still faces various socio-economic challenges, such as poverty, fatigue, and limited infrastructure. In addition, this research shows that the district's development is influenced by several factors, including political will, institutional capacity, and community participation. The contribution of this research includes providing a thorough understanding of the socio-economic conditions and potential development of Bima Regency, as well as identifying the key factors influencing its development. Policy implications and practices emphasize the need to increase institutional capacity, improve infrastructure, and promote community participation in district development. Limitations of this study include the small sample size and limited data collection period. Future research should address these limitations by using larger sample sizes and longer data collection periods. Overall, this study provides valuable insights into the socio-economic conditions and development potential of the Bima district, and the pressures for policy interventions to enhance the district's development.